Animal baths : wild & wonderful ways animals get clean! - Fielding, Beth (EarlyLight Books, 2009)
Discover the wild and wonderful ways animals get clean. Some animals get really dirty to get clean and some get other animals to clean them. Others just ditch their dirty skin.